2020
DOI: 10.3390/ijerph17145130
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Palliative and End-Of-Life Care in Hong Kong: Perspectives of Healthcare Providers

Abstract: Background: In response to population aging, there is a need for health systems to focus on care for chronic disease, specifically palliative care, while focusing on people-centered care. The objective of this study is to explore the healthcare system enablers and barriers to the provision of quality palliative and end-of-life care from the perspective of healthcare professionals. Materials and Methods: Using purposive sampling, fifteen focus group interviews and nine individual interviews involving 72 healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In summary, although there were various practices and providers of EOL care in Hong Kong, as summarized in the Introduction section, there is no overarching policy framework related to EOL care that conceptualizes and clarifies patients’ and their family members’ holistic needs, and how they could be provided with a comprehensive system of care. An advantage of the present study is that it extended from previous works that focused primarily on perspectives from the care providers [ 33 , 34 ]. While there are consistent findings, the present study also encompasses opinions and observations of other major stakeholders of EOL care including the non-care providers.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, although there were various practices and providers of EOL care in Hong Kong, as summarized in the Introduction section, there is no overarching policy framework related to EOL care that conceptualizes and clarifies patients’ and their family members’ holistic needs, and how they could be provided with a comprehensive system of care. An advantage of the present study is that it extended from previous works that focused primarily on perspectives from the care providers [ 33 , 34 ]. While there are consistent findings, the present study also encompasses opinions and observations of other major stakeholders of EOL care including the non-care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in qualitative studies about end-of-life care in the literature, similar themes such as continuing to have hope, providing spiritual care, adopting a multidisciplinary approach, cooperating with the patient and their family, providing also the family with psychosocial support and preparing the family for the mourning process have come forward (Brooks et al, 2017 ; Dalal & Bruera, 2017 ; Dong et al, 2016 ; Liu & Chiang, 2017 ). Nurses who provided end-of-life care have thought that, to provide good-quality end-of-life care, pain should be alleviated, physical care should be continued properly, effective teamwork should be in place, and the patient and their family should be provided with physical and emotional peace and spiritual comfort (Huang et al, 2016 ; Kisorio & Langley, 2016 ; Wong et al, 2020 ). It was found that one of the points the students underlined most in end-of-life care was the necessity to put the patient’s pain/ache under control.…”
Section: Discussionmentioning
confidence: 99%
“…The survey showed that there is room for improvement in self-competence in death work among health and social care workers, especially among the younger age group, nurses, and those working in acute hospitals ( 29 ). There were also barriers to advance care planning from the patients’ and families point of view ( 30 ), and implementation of service changes ( 31 , 32 ). These studies showed that improvement in end of life care is needed in promotion and training end of life care conversations for health and social care professionals as well as patients and families, and fit for purpose services in both the institutional and community settings.…”
Section: Raising Capacity In Hospitalsmentioning
confidence: 99%